Among English, Indonesian and local language: Translanguaging practices in an Indonesian EFL classroom - Nihta V. F. Liando; Ruswan Dallyono; Devilito P. Tatipang; Fergina Lengkoan (Universitas Pendidikan Indonesia, 2023)
Teaching English as a foreign language (EFL) in Indonesia has its own complexity due to the multilingual situation and the broadly different levels of English proficiency.Â To cope with this particular challenge, some Indonesian teachers tend to use a translanguaging method in teaching their students so that their classes are more interactive and engaging. In this case, translanguaging is a form of multilingual practice in the context of multilingual education where students are given equal rights to develop their language potential. Realizing the complexity of the learning process in a multilingual context, we aimed to reveal the types and purposes of Translanguaging in the learning process. This study used a qualitative method and data were collected through observations, interviews, and document analyses. This study shows that there were three types of translanguaging used by teachers during their teaching. The types of translanguaging are intra-sentential translanguaging, intersentential translanguaging, and tag translanguaging, with four purposes inform of strategies that are related to each other. It was also found that translanguaging is useful in the EFL learning processes because it can be used as a method to explain learning materials in a more convenient way to enhance studentsâ€™ understanding.